Accident Risk Analysis at Level Crossings Based on Physical and Operational Characteristics (Case Study: Crossing Points in Medan City Area): Application of the ALCAM Model in Medan City - Hamdani, Aldi BJ; Amrozi, Mukhammad Rizka Fahmi (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Level crossings are critical safety points in railway operations due to the interaction between trains and road traffic. In Indonesia, many crossings in urban areas such as Medan operate with limited safety infrastructure, increasing the likelihood of serious accidents. This study aims to evaluate accident risks and propose mitigation strategies for selected level crossings in Medan. A quantitative risk assessment was conducted using the Australian Level Crossing Assessment Model (ALCAM), which considers infrastructure, exposure, and consequence factors. Data were collected through field observations, interviews with crossing attendants, and secondary records from local transport authorities. Three locations were analyzed: KM 9+30 on the Medan–Binjai line, and JPL 1 (KM 0+640) and JPL 4 (KM 1+325) on the Medan–Tanjung Balai line. The ungated crossing at KM 9+30 had a risk score of 0.053, JPL 1 the highest at 0.136, and JPL 4 at 0.076. Simulated mitigation strategies substantially reduced risks to 0.020, 0.051, and 0.038, respectively. These findings demonstrate that ALCAM provides a reliable framework for quantifying risks and prioritizing safety improvements at level crossings in Indonesia.